Determinants of female sterilization method uptake among women of reproductive age group in Uganda - Paula Anita; Abel Nzabona; Richard Tuyiragize (BMC, 2020)
Abstract Background Despite its great effectiveness, safety and convenience for women who do not wish to have more children; female sterilization method uptake in Uganda is very low. This study aimed at establishing factors associated with female sterilization uptake in Uganda. Methods Secondary data were sourced from the 2016 Uganda Demographic and Health Survey (UDHS). We analyzed all (18,506) women aged 15-49 years who were interviewed in the 2016 UDHS. This sample was categorized into women who were sterilized and those using other modern methods. We used a Chi-square test to measure the association between the current uptake of female sterilization by the women and selected independent variables. Multivariate analysis applied the complimentary log-log model to determine the net effect of selected characteristics on female sterilization uptake in Uganda. Results The overall prevalence of female sterilization among modern contraceptive users was 2%. Female sterilization uptake was highly associated with age of 30 years and older (OR = 34.49;, 95%CI:13.33-99.88), middle wealth status (OR = 0.65, 95% CI:0.47-0.92), women who had ever given birth to at least four children (OR = 3.19, 95% CI:1.63-6.22) and decision making by either the husband/partner (OR = 2.42, 95% CI:1.55-3.78) or jointly between a woman and her husband/partner (OR = 1.38, 95% CI:1.02-1.86). Conclusions The uptake of female sterilization was very low, and this was associated with; age, household wealth, parity and contraceptive decision-maker. The uptake of Family planning programs needs to focus on male engagement to increase joint decision making on family planning issues especially those relating to fertility limitation. Government and its other implementing partners need to scale-up efforts that increase accessibility to information on female sterilization services for women who have completed their fertility.